Focal Cortical Dysplasia IIIa in Hippocampal Sclerosis-Associated Epilepsy: Anatomo-Electro-Clinical Profile and Surgical Results From a Multicentric Retrospective Study. (18th November 2021) - Cossu, Massimo; d'Orio, Piergiorgio; Barba, Carmen; Asioli, Sofia; Cardinale, Francesco; Casciato, Sara; Caulo, Massimo; Colicchio, Gabriella; Consales, Alessandro; D'Aniello, Alfredo; De Benedictis, Alessandro; De Palma, Luca; et al.
Graphical Abstract: